I think I am getting better at this. Differentiate the given function: f(x) = 1/4*x^8 - 1/2 *x^6 - x + 2 f'(x) = 1/4(8x^7) - 1/2(6*x^5) - 1 f"(x) = 2(x^7) -3(x^5) -1
Follow Math Help Forum on Facebook and Google+
Originally Posted by becky I think I am getting better at this. Differentiate the given function: f(x) = 1/4*x^8 - 1/2 *x^6 - x + 2 f'(x) = 1/4(8x^7) - 1/2(6*x^5) - 1 f"(x) = 2(x^7) -3(x^5) -1 What happend here? $\displaystyle f''(x)=2x^7-3x^5-1$ You probably meant to write, $\displaystyle f'(x)=2x^7-3x^5-1$. That is the simplification of, $\displaystyle 1/4(8x^7)-1/2(6x^5)-1$
I meant to write: f'(x)
View Tag Cloud